THU0401 Ultrasound evaluation in follow-up of urate-lowering therapy in gouty patients: the useful study. (15th June 2017) - Forien, M; Norkuviene, E; Richette, P; Mouterde, G; Ea, H-K; Lioté, F; Petraitis, M; Bardin, T; Ora, J; Dieudé, P; Ottaviani, S
Abstract : Background: Ultrasonography (US) has demonstrated its ability to detect urate deposition in gouty patients. Some US features have been suggested to be specific such as tophus and the double contour (DC) sign. In contrast to the usefulness of US for diagnosis, data are lacking on its role in follow-up of gout deposition after initiation of urate-lowering therapy (ULT). Objectives: We aimed to determine the ability of US to show disappearance of urate deposits in gouty patients requiring ULT. Methods: We performed a 6-month multicentre prospective study. To be included in the study, patients needed to have: i) a proven gout (identification of monosodic urate crystal in synovial fluid analysis or tophus aspiration), ii) presence of US features of gout (tophus and/or DC sign) at knee and/or first metatarsophalangeal joints (MTP1s). Serum uric-acid (SUA) level was assessed at baseline, M3 and M6. US evaluations were performed at baseline, M3 and M6 after starting ULT, by one local rheumatologist, blinded to SUA levels and clinical data. The primary outcome was the decrease (absolute value and percentage of decrease) of US tophus after 6 months of ULT, according to the final SUA levels. The secondary outcome was the mean percentage of joint sites with DC sign disappearance. Three stages of SUA levels were defined (high SUA levels: >360 μmol/l, low SUA: 300 -360 μmol/l, very low SUA: <300 μmol/l. Results: A total of 79 gouty patients (mean ± SD age 61.8±14 years, 91% of males) were included. The mean disease duration was 6.3±6.1 years. Tophi were found at clinical exam in 29% of patients. Baseline SUA levels were 530±97 μmol/l. At least one US tophus and DC sign were found in 74 (93.7%) and 68 (86.1%) of patients, respectively. Allopurinol and febuxostat was started in 26 (33%) and 53 (67%) patients, respectively. A total of 67 patients were completers at 6 months. Among those M6 completers, 39 and 18 patients achieved a very low and low SUA levels, respectively. The 10 remaining patients maintained high SUA levels. Comparison of US features of gout modifications between the 3 groups of final SUA levels revealed a higher decrease of US tophus size and higher proportion of DC sign dissolution among patients with lowest SUA levels (Table 1 ). Additionally, final M6 SUA levels was associated with: decrease size of tophus (r=0.5093 [0.3012; 0.6711], P<0.0001), percentage of decrease of the tophus size (r=0.5352 [0.3332; 0.6902], P<0.0001) and inversely correlated with the proportion of DC sign dissolution (r=-0.624 [-0.763; -0.4298]). Conclusions: US is able to detect decrease or disappearance of US urate deposits after ULT. Additionally, the decrease of US deposits is strongly correlated with lowest SUA levels. These data suggest that US could be useful for ULT management in gouty patients. Disclosure of Interest: None declared